Persepsi Siswa terhadap Penggunaan Media Teknologi Interaktif dalam Pembelajaran PJOK di SMP Muhammadiyah 1 Surakarta - Muhammad Yoga Pamungkas; Pungki Indarto; Eko Sudarmanto (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aimed to describe students’ perceptions of the use of interactive technology media in Physical Education, Sports, and Health (PJOK) learning at SMP Muhammadiyah 1 Surakarta. The study used a qualitative method with a case study design. The participants consisted of 5 students from class VII SDC 2 and 1 PJOK teacher selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation during PJOK learning on the underhand volleyball passing material using interactive presentations, learning videos, and tablet-based digital quizzes. The data were analyzed using thematic analysis with source and method triangulation to ensure data validity. The results showed that students had positive perceptions toward the use of interactive technology media in PJOK learning. Learning videos helped students understand the material visually, while digital quizzes increased students’ motivation, engagement, and enthusiasm during the learning process. Supporting factors included the availability of tablets, internet access, and LCD projectors, while inhibiting factors included technical device constraints and the limited implementation of technology in PJOK learning dominated by field practice activities. The use of interactive technology media can support more interesting and effective PJOK learning, especially for theoretical materials.